Coffee Shop Loyalty Model: A Review - Nandang Suhada Yasir Mansur (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
The coffee shop industry has experienced significant growth over recent years, driven by changing consumer preferences and the rise of café culture. In this competitive environment, building customer loyalty has become a crucial aspect for long-term business sustainability. This review explores the various models and frameworks used to understand and enhance customer loyalty in coffee shops. It analyzes key factors influencing loyalty, including service quality, product satisfaction, price perception, and emotional connection with the brand. Additionally, the role of technological innovations such as loyalty programs and mobile apps is discussed, highlighting how they contribute to increased customer retention and engagement. The paper also examines the importance of personalized experiences, social media influence, and the impact of brand image on loyalty formation. By reviewing existing literature and case studies, this study aims to provide insights into effective strategies for developing and maintaining loyalty in coffee shop businesses. The findings suggest that a holistic approach, combining both traditional and digital strategies, is essential for fostering strong customer loyalty in today's dynamic market.